Political overtures the songs of Yano counternarratives - Moratilla, Noel Christian A. (2011)
One of the influential local bands of the 1990's, Yano produced and performed songs on social and political themes such as the EDSA revolt, religious hypocrisy, and the failings of the educational sector. Unlike many of their contemporaries, Yano chose to politicize their music, that is, by fusing upbeat and aggressive melodies with lyrics about social problems and concerns. Deploying elements of parody and sarcasm, the songs may be seen as counter narratives exposing and negotiating the complications of the social structure. Given that many of the issues addressed by the songs remain unresolved, the music of Yano can be constitutive of alternative literary practices for exposing and countering these unsettling and unsettled tensions.
Keywords: Yano (Band); Songs